THE ASSESSMENT OF THE IMPLEMENTATION OF BUILDING INFORMATION MODELLING (BIM) AND INTEGRATED PROJECT DELIVERY (IPD) IN THE CONSTRUCTION INDUSTRY: A CASE STUDY IN PAKISTAN - Moaaz Munir; Ali Ajwad; Usama Khan; Salman Ali Suhail; Usman Ilyas; Muhammad Akhtar (Spectrum of Engineering Sciences, 2025)
This research explores the implementation and impact of Building Information Modelling (BIM) and Integrated Project Delivery (IPD) within Pakistan’s construction industry, examining how these methodologies could enhance project outcomes. Utilizing a quantitative survey, the study gathered data from industry professionals to evaluate the extent of BIM and IPD utilization, assess perceptions, and identify barriers to implementation. The results reveal that BIM adoption in Pakistan is notably low, with an estimated implementation rate of just 11% nationally, while findings from this study indicate an even lower rate among surveyed firms. Key challenges identified include a significant shortage of skilled professionals, insufficient training opportunities, and the high initial costs related with BIM technologies. Despite a growing awareness of the benefits of BIM and IPD, substantial gaps remain in their practical application, with many professionals still unfamiliar with or resistant to these modern methods. A comparative analysis with global adoption rates underscores a stark disparity between developed and developing nations. While developed countries have seen widespread integration of BIM and IPD, driven by government mandates and advanced infrastructure, developing countries like Pakistan face considerable hurdles. These include a lack of standardized practices, inadequate regulatory support, and limited resources for training and development. The study concludes that addressing these barriers is critical in maximizing the potential of BIM and IPD in Pakistan. Government support, through policy initiatives and incentives, combined with enhanced educational and training programs, is essential for overcoming the current obstacles. By focusing on these areas, Pakistan can fully leverage BIM and IPD to enhance efficiency and support the overall economic growth of the construction sector.